Diabetes care quality according to facility setting: A cross-sectional analysis in six Peruvian regions - Calderon-Ticona J.R. (2021)
Objective: To characterize diabetes care across healthcare facilities in six Peruvian regions. Methods: Cross-sectional study of patients with type 2 diabetes mellitus (T2DM), ranging from primary care facilities to hospital-based facilities, in six Peruvian regions. Data was collected by health staff trained between 2012 and 2016. We studied six diabetes care outcomes and four adequate diabetes care outcomes considering the healthcare facility as the exposure of interest. We estimated prevalence ratios (PR) and their 95% confidence intervals (95% CI) using Poisson regression with robust variance. Results: Data from 8879 patients with T2DM, mean age 59.1 years (SD ± 12.2), 53.6% males, was analyzed. Of these, 8096 (91.2%) were treated at primary care facilities. The proportions of patients who had HbA1c, LDL-c, and creatinine/microalbumin test performed increased with the setting of the healthcare facility. Overall, 39%–56% of patients had an adequate HbA1c control, being higher in hospital-based facilities with specialists in comparison to primary care facilities. Conclusions: We observed that the higher the setting of the facility, the higher the rate of the assessed diabetes care outcomes and adequate diabetes care for four of the six targets (fasting glucose, HbA1c, LDL-c and creatinine or microalbumin) and for three of the four targets (glucose?130 mg/dL, HbA1c ?7%(53 mmol/mol) and LDL-c <100 mg/dL), respectively. Substantial gaps were observed at the primary care facilities, calling for the strengthening of diabetes care. © 2020 Primary Care Diabetes Europe